Suppose,

\(\displaystyle f(x) = \sum_{n=0}^{\infty} f_n x^n\), \(\displaystyle F(n) = \sum_{r=0}^{n} f_{r}\) and \(\displaystyle \lim_{n \to \infty} \dfrac{F(n)}{n^{r_f}} = \text{d}_f \)

Similarly,

\(\displaystyle g(x) = \sum_{n=0}^{\infty} g_n x^n\), \(\displaystyle G(n) = \sum_{r=0}^n g_r\) and \(\displaystyle \lim_{n \to \infty} \dfrac{G(n)}{n^{r_g}} = \text{d}_g \)

From Monster Limit 2, we have,

\[\begin{cases} \lim_{x \to 1^{-}} (1-x)^{r_f} \ f(x) = \text{d}_f \ \Gamma(1+r_f)\\ \lim_{x \to 1^{-}} (1-x)^{r_g} \ g(x) = \text{d}_g \ \Gamma(1+r_g) \end{cases}\]

Now, consider the same quantities for \(fg(x) = f(x)g(x)\), i.e,

\(\displaystyle fg(x) = \sum_{n=0}^{\infty} {fg}_n x^n\), \(\displaystyle FG(n) = \sum_{r=0}^{n} {fg}_{r}\) and \(\displaystyle \lim_{n \to \infty} \dfrac{FG(n)}{n^{r_{fg}}} = \text{d}_{fg} \)

Again,

\(\displaystyle \lim_{x \to 1^{-}} (1-x)^{r_{fg}} \ fg(x) = \text{d}_{fg} \ \Gamma(1+r_{fg})\)

Prove That

\[\displaystyle \text{d}_{fg} = \text{d}_{f} \text{d}_{g} \dfrac{\Gamma(1+r_f) \Gamma(1+r_g)}{\Gamma(1+r_f + r_g)}\]

No vote yet

1 vote

×

Problem Loading...

Note Loading...

Set Loading...

Easy Math Editor

`*italics*`

or`_italics_`

italics`**bold**`

or`__bold__`

boldNote: you must add a full line of space before and after lists for them to show up correctlyparagraph 1

paragraph 2

`[example link](https://brilliant.org)`

`> This is a quote`

Remember to wrap math in \( ... \) or \[ ... \] to ensure proper formatting.`2 \times 3`

`2^{34}`

`a_{i-1}`

`\frac{2}{3}`

`\sqrt{2}`

`\sum_{i=1}^3`

`\sin \theta`

`\boxed{123}`

## Comments

There are no comments in this discussion.